2012
DOI: 10.1261/rna.033233.112
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing of protein sequences: A rare event in human transcriptomes

Abstract: RNA editing, the post-transcriptional recoding of RNA molecules, has broad potential implications for gene expression. Several recent studies of human transcriptomes reported a high number of differences between DNA and RNA, including events not explained by any known mammalian RNA-editing mechanism. However, RNA-editing estimates differ by orders of magnitude, since technical limitations of high-throughput sequencing have been sometimes overlooked and sequencing errors have been confounded with editing sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 51 publications
(98 reference statements)
6
50
2
Order By: Relevance
“…Among these positions, only 20.9% of the nuclear and 32.7% of the cytosolic editable sites were specific to one cell line, indicating cell-line-specific regulation of editing. In contrast to the poor consistency across cell lines or even biological replicates reported in previous studies (14,19), our results suggest that many editing sites are indeed shared by multiple cell lines if we take into account the expression difference and the sampling fluctuation in read coverage.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Among these positions, only 20.9% of the nuclear and 32.7% of the cytosolic editable sites were specific to one cell line, indicating cell-line-specific regulation of editing. In contrast to the poor consistency across cell lines or even biological replicates reported in previous studies (14,19), our results suggest that many editing sites are indeed shared by multiple cell lines if we take into account the expression difference and the sampling fluctuation in read coverage.…”
Section: Resultscontrasting
confidence: 99%
“…These results suggest that targetenrichment strategies for weakly expressed genes are urgently needed for editing analysis. The previously reported poor consistency across cell lines or even biological replicates put the biological significance and the importance of global editing under suspicion (14,19). Our study, however, shows that the poor consistency is mainly due to the sensitivity of editing discovery to sequencing depths.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A-to-G substitution is typically the most frequently occurring RNA variants detected in other RNA editing studies (22)(23)(24)(25). Curiously, we found that after T-to-C, A-to-G substitutions were the more frequent substitutions identified in our study (Fig.…”
Section: Rna Variation Is Similar In Drug-tolerant Cells and Other Casupporting
confidence: 72%
“…In the last few years, genomic studies in humans have uncovered an astonishingly large number of RNA editing sites (4,(14)(15)(16)(17)(18)(19)(20). Although editing apparently occurs primarily in noncoding regions, especially in Alu repeat elements (15,19,20), the number of edited coding sites also exceeds 100 times the previously known number (14).…”
mentioning
confidence: 99%